Ambient Fabrication of Large‐Area Graphene Films via a Synchronous Reduction and Assembly Strategy. (19th April 2013) - Cao, Xuebo; Qi, Dianpeng; Yin, Shengyan; Bu, Jing; Li, Fengji; Goh, Chin Foo; Zhang, Sam; Chen, Xiaodong
<x xml:space="preserve">Abstract</x> A synchronous reduction and assembly strategy is designed to fabricate large‐area graphene films and patterns with tunable transmittance and conductivity. Through an oxidation–reduction reaction between the metal substrate and graphene oxide, graphene oxide is reduced to chemically converted graphene and is organized into highly ordered films in situ. This work will form the precedent for industrial‐scale production of graphene materials for future applications in electronics and optoelectronics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>